Puffing/micro-explosion in droplets of rapeseed oil with coal micro-particles and water - Antonov D. V. Dmitry Vladimirovich; Kuznetsov G. V. Geny Vladimirovich; Sazhin S. S. Sergey Stepanovich; Strizhak P. A. Pavel Alexandrovich (2022, 2022)
Title screen